2019
DOI: 10.1002/adma.201900353
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Borophene and Its Hybrids

Abstract: Borophene, an elemental metallic Dirac material is predicted to have unprecedented mechanical and electronic character. Need of substrate and ultrahigh vacuum conditions for deposition of borophene restricts its large‐scale applications and significantly hampers the advancement of research on borophene. Herein, a facile and large‐scale synthesis of freestanding atomic sheets of borophene through a novel liquid‐phase exfoliation and the reduction of borophene oxide is demonstrated. Electron microscopy confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
245
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 252 publications
(266 citation statements)
references
References 35 publications
8
245
1
Order By: Relevance
“…Experimental research revealed that the interaction between χ 3 borophene and Ag(111) was very weak . Monolayer freestanding χ 3 borophene was also realized by facile sonochemical exfoliation . From the phonon band dispersion in Figure , we also found that the cutoff frequency of those borophene sheets was about 1200–1400 cm −1 , comparable to that of graphene (1600 cm −1 ) .…”
Section: Thermal Transport Of Borophenementioning
confidence: 76%
See 4 more Smart Citations
“…Experimental research revealed that the interaction between χ 3 borophene and Ag(111) was very weak . Monolayer freestanding χ 3 borophene was also realized by facile sonochemical exfoliation . From the phonon band dispersion in Figure , we also found that the cutoff frequency of those borophene sheets was about 1200–1400 cm −1 , comparable to that of graphene (1600 cm −1 ) .…”
Section: Thermal Transport Of Borophenementioning
confidence: 76%
“…Therefore, β 12‐ borophene is highly to be stabilized by a suitable substrate. Recent experiment showed that the freestanding β 12 borophene has parallel ridges rather than flat structure and the ridge was found to be important for the stability of this structure . Among these explored structures in this paper, only the flat χ 3 borophene sheet is stable without external strain.…”
Section: Thermal Transport Of Borophenementioning
confidence: 82%
See 3 more Smart Citations